Investigations on DNA intercalation and surface binding by SYBR Green I, its structure determination and methodological implications - Zipper, Hubert (Oxford University Press, 2004)
The detection of double-stranded (ds) DNA by SYBR Green I (SG) is important in many molecular biology methods including gel electrophoresis, dsDNA quantification in solution and real-time PCR. Biophysical studies at defined dye/base pair ratios (dbprs) were used to determine the structure–property relationships that affect methods applying SG. These studies revealed the occurrence of intercalation, followed by surface binding at dbprs above ∼0.15. Only the latter led to a significant increase in fluorescence. Studies with poly(dA) · poly(dT) and poly(dG) · poly(dC) homopolymers showed sequence-specific binding of SG. Also, salts had a marked impact on SG fluorescence. We also noted binding of SG to single-stranded (ss) DNA, although SG/ssDNA fluorescence was at least ∼11-fold lower than with dsDNA. To perform these studies, we determined the structure of SG by mass spectrometry and NMR analysis to be [2-[N-(3-dimethylaminopropyl)-N-propylamino]-4-[2,3-dihydro-3-methyl-(benzo-1,3-thiazol-2-yl)-methylidene]-1-phenyl-quinolinium]. For comparison, the structure of PicoGreen (PG) was also determined and is [2-[N-bis-(3-dimethylaminopropyl)-amino]-4-[2,3-dihydro-3-methyl-(benzo-1,3-thiazol-2-yl)-methylidene]-1-phenyl-quinolinium](+). These structure–property relationships help in the design of methods that use SG, in particular dsDNA quantification in solution and real-time PCR.